Analysis of tissue and serum microRNA expression in patients with upper urinary tract urothelial cancer. - Stephanie Kriebel; Doris Schmidt; Stefan Holdenrieder; Diane Goltz; Glen Kristiansen; Rudolf Moritz; Christian Fisang; Stefan C Müller; Jörg Ellinger (PLoS ONE, 2015)
INTRODUCTION:MicroRNAs play an important role in many human malignancies; so far, their expression remains to be studied in upper urinary tract urothelial cancer (UUTUC). MATERIALS AND METHODS:The expression of eleven microRNAs (miR-10a, miR-21, miR-96, miR-135, miR-141, miR-182, miR-200b, miR-205, miR-429, miR-520b, miR-1244) formerly shown to be upregulated in urothelial bladder cancer were studied in corresponding normal and cancerous tissue samples of patients undergoing nephroureterectomy for UUTUC. Upregulated microRNAs were then measured in serum samples of patients with UUTUC and patients with non-malignant urological diseases to evaluate their potential as non-invasive biomarkers for UUTUC. RESULTS:MicroRNA expression allowed differentiation of normal and cancerous tissue: miR-21, miR-96, miR-135, miR-141, miR-182, miR-205, miR-429 and miR-520b were significantly overexpressed. Furthermore, miR-205 was upregulated in poorly differentiated UUTUC. The analysis of circulating RNA in serum demonstrated an increase of miR-141 in patients with UUTUC; receiver operator characteristic analysis demonstrated an area under the curve of 0.726 for miR-141 as a diagnostic biomarker. Furthermore, we observed lower levels of miR-10a and miR-135 in UUTUC patients. CONCLUSIONS:MicroRNA expression is altered in UUTUC. The analysis of circulating miR-141 may be useful to identify patients with UUTUC.